Validation of the Need for Competing Inventory - Bugten, Jesper B.; Lugo, Ricardo G.; Steptoe, Karl (Frontiers in Psychology, 2021)
Past studies have been conducted on competitiveness and the achievement orientation as two noncooperative explanations for achievement motivation and achievement behavior. But a complimentary representation of a competitive-achievement orientation was yet to be explored. This paper developed and validated the need for competing inventory (NCI), and further investigated its relations with achievement orientation, emotional assessment, self-efficacy, grit, anxiety, and flow. The results from the present study supports the theoretical construct of the need for competing, hoping it will give a solid foundation for a competitive-achievement orientation, which is suggested to play a significant role in competitive achievement behavior. Hopefully, the results from the present study will open a debate for including a competitive-achievement orientation in future research with the aim for a stronger predictor for achievement behavior.